2014
DOI: 10.1097/mpa.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction of the Peripancreatic Vascular System Based on Computed Tomographic Angiography Images and Its Clinical Application in the Surgical Management of Pancreatic Tumors

Abstract: A peripancreatic vascular reconstruction can reveal the vascular anatomy, variations of peripancreatic vascular, and tumor-induced vascular changes; the application of the simulation surgery platform could reduce surgical trauma and decrease operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
0
25
0
3
Order By: Relevance
“…Developments in computer science and its integration with medical imaging technology offer a novel opportunity to reduce these adverse events by visualizing the intrahepatic vessels and optimizing resection schemes on individual 3D models. The application of MI-3DVS in observing the origin, bifurcations, and anatomical variations of blood vessels and the relationship between the tumor and crucial surrounding structures have been described previously [ 17 20 ]. This technology plays an important role in volumetric analysis and characterizing the anatomical features of hepatolithiasis, liver cancer, and pancreatic disease [ 7 , 8 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in computer science and its integration with medical imaging technology offer a novel opportunity to reduce these adverse events by visualizing the intrahepatic vessels and optimizing resection schemes on individual 3D models. The application of MI-3DVS in observing the origin, bifurcations, and anatomical variations of blood vessels and the relationship between the tumor and crucial surrounding structures have been described previously [ 17 20 ]. This technology plays an important role in volumetric analysis and characterizing the anatomical features of hepatolithiasis, liver cancer, and pancreatic disease [ 7 , 8 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of MI-3DVS in observing the origin, bifurcations, and anatomical variations of blood vessels and the relationship between the tumor and crucial surrounding structures have been described previously [ 17 20 ]. This technology plays an important role in volumetric analysis and characterizing the anatomical features of hepatolithiasis, liver cancer, and pancreatic disease [ 7 , 8 , 17 , 21 ]. In other words, major drawbacks of conventional hepatectomy, such as compromised liver function and high incidence of complications could be overcome or at least minimized through adequate preservation of liver parenchyma and comprehensive preoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Another study, exploring the effects of 3D reconstruction of peripancreatic vascular system on pancreatic surgeries, found that this novel application could apparently reduce surgical trauma and decrease operative time. 13 Although the 3D technology has achieved initial success in clinical application, it is still not systematically introduced into the standardized residency training. Thus, we designed this study to explore the value of 3D visualized pancreatic model in tumor evaluation and surgery planning for surgical trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Avec l'angio-TDMMD 3D, le taux de visualisation des artères péripancréatiques est de 86,6 % pour l'artère pancréaticoduodénale antérosupérieure, de 85,0 % pour l'artère pancréaticoduodénale postérosupérieure, de 76,6 % pour l'artère pancréaticoduodénale antéro-inférieure, de 71,6 % pour l'artère pancréaticoduodénale postéro-inférieure, de 91,6 % pour l'artère pancréatique dorsale et de 53,3 % pour la branche artérielle marginale supérieure de la tête du pancréas [64]. Une angio-TDMMD 3D en préopératoire révèle des variations des artères péripancréatiques et des modifications vasculaires induites par la tumeur, ce qui permet de raccourcir la durée de l'intervention, de diminuer les pertes sanguines et de réduire le taux des complications peropératoires [64].…”
Section: Tumeur Pancréatiqueunclassified
“…Une angio-TDMMD 3D en préopératoire révèle des variations des artères péripancréatiques et des modifications vasculaires induites par la tumeur, ce qui permet de raccourcir la durée de l'intervention, de diminuer les pertes sanguines et de réduire le taux des complications peropératoires [64].…”
Section: Tumeur Pancréatiqueunclassified